2005
DOI: 10.1073/pnas.0507351102
|View full text |Cite
|
Sign up to set email alerts
|

A microscopic view of miniprotein folding: Enhanced folding efficiency through formation of an intermediate

Abstract: The role of polypeptide collapse and formation of intermediates in protein folding is still under debate. Miniproteins, small globular peptide structures, serve as ideal model systems to study the basic principles that govern folding. Experimental investigations of folding dynamics of such small systems, however, turn out to be challenging, because requirements for high temporal and spatial resolution have to be met simultaneously. Here, we demonstrate how selective quenching of an extrinsic fluorescent label … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
211
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(234 citation statements)
references
References 38 publications
22
211
0
1
Order By: Relevance
“…The physico-chemical origins of the fluctuations in the fluorescence signal of apoMb V1C-AL488 are attributed to interactions of the N-terminal Alexa 488 label with amino acids at various parts of the protein chain that quench the fluorescence emission of the dye. Because quenching is a short-range interaction (Ͻ2 Å) (46), we assume that quenching events occur via van der Waal's contact between the dye and quencher on a time scale faster than is resolved in these measurements (19). Although the specific quenching mechanisms are not the focus of this study, we did determine which amino acids are most likely to be involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The physico-chemical origins of the fluctuations in the fluorescence signal of apoMb V1C-AL488 are attributed to interactions of the N-terminal Alexa 488 label with amino acids at various parts of the protein chain that quench the fluorescence emission of the dye. Because quenching is a short-range interaction (Ͻ2 Å) (46), we assume that quenching events occur via van der Waal's contact between the dye and quencher on a time scale faster than is resolved in these measurements (19). Although the specific quenching mechanisms are not the focus of this study, we did determine which amino acids are most likely to be involved.…”
Section: Discussionmentioning
confidence: 99%
“…Although commonly used to measure the diffusion-associated properties of biomolecules, FCS can also characterize fluctuations in fluorescence intensity caused by chemical kinetics or photophysics (4)(5)(6)(7)(9)(10)(11). A number of studies have demonstrated the utility of FCS in monitoring folding or functionrelated conformational fluctuations in RNA (12,13), DNA (14)(15)(16)(17)(18), polypeptides (19), and, of particular interest to this study, proteins (20)(21)(22)(23)(24). Chattopadhyay et al (20,21) followed a pH-induced unfolding transition in a small fatty acid binding protein, finding that the decrease of the amplitude of a Ϸ35-s fluctuation mirrored the unfolding of the protein and later demonstrating that their observed motions were diffusive in nature.…”
mentioning
confidence: 99%
“…However, other folding mechanisms have been proposed. Neuweiler et al 17 utilizing fluorescence correlation spectroscopy (FCS), proposed a more complex folding process with a collapsed molten globule-like intermediate as well as conformational flexibility of Trp-cage in the denatured state. This is in line with UV resonance Raman spectroscopy (UVRS) results carried out by Ahmed et al, 18 who proposed the presence of an intermediate with an intact α-helix, where the hydrophobic core is even more compact.…”
Section: Introductionmentioning
confidence: 99%
“…14 Notwithstanding its small size, Trpcage contains typical protein motifs, an α-helix (residue 2-8), a 3 10 -helix (residue [11][12][13][14], and a polyproline II helix (residue [17][18][19], which form a hydrophobic core with the tryptophan buried in the center.…”
Section: Introductionmentioning
confidence: 99%
“…Laser temperaturejump spectroscopy experiments by Qiu et al (5) indicated two-state folding. Subsequently, fluorescent correlation spectroscopy by Neuweiler et al (6) revealed that the protein (un)folds in a more complicated manner via an intermediate molten globule-like state, characterized by exposure of the tryptophan to the solvent. It remains unclear at what stage of folding the helix is being formed.…”
mentioning
confidence: 99%